Intravenous Ketamine for Refractory Bronchospasm Precipitated by H1N1 Infection - Agrawal, Amit; Shrivastava, Jyotsna (Frontiers in Pediatrics, 2014)
Acute severe bronchospasm is an emergency situation and sometimes these children may fail to respond to conventional treatment and deteriorate rapidly to respiratory failure requiring mechanical ventilation. We present a case of 2-year-old girl, who presented with severe bronchospasm resulting in respiratory failure not responding to conventional management including mechanical ventilation and was found to be H1N1 positive. She was treated with ketamine infusion, which led to prompt improvement in airway obstruction.